Effect of titanium pick-up on mould flux viscosity in continuous casting of titanium-stabilised stainless steel - Pistorius, Petrus Christiaan (University of Pretoria, 2013)
Dissertation (M Eng (Metallurgical Engineering))--University of Pretoria, 2006.